Pengembangan Sistem Arsip Digital dalam Meningkatkan Pelayanan Publik Menggunakan Extreme Programming - Arisantoso Arisantoso; Jefri Rahmadian; Harriansyah Harriansyah; Dwi Sidik Permana; Imam Ahmad (Tech-E, 2022)
The process of filing a letter is usually done by recording it in an archive book, then the letter is stored in a place or filing cabinet that has been provided. This is considered not optimal, in providing correspondence services that are needed by the community. Due to the limited staff working in the village office, the process takes a long time. This research discussed how to create and design digital archive applications and correspondence starting from data collection methods (interviews, observations and documentation) using extreme programming development methods, system design using UML with Use case Diagram design model, and CRC Card. TRITAM model test results that have been conducted involving 16 respondents showed results of 82.56% with good criteria. From the results of these tests showed good results for prototype users for the mail filing system.